PENGARUH KETERAMPILAN KERJA, KOMITMEN KERJA DAN BUDAYA KERJA TERHADAP PENILAIAN PRESTASI KERJA SERTA IMPLIKASINYA PADA EFEKTIVITAS KERJA PEGAWAI DINAS PERTANIAN KOTA PAGAR ALAM: The Influence of Skills, Commitment and Culture on Work Performance of Agricultural Service Employees in Pagar Alam City - Aprini, Nisma; Aminah, Aminah; Hardiyansyah, Hardiyansyah (Enviagro: Jurnal Pertanian dan Lingkungan, 2023)
The author conducted research with the aim of knowing and analyzing the effect of work skills, work commitment and work culture on work performance evaluation and their implications for the work effectiveness of the Agriculture Office of the City of Pagar Alam. The research method used in this study is a quantitative method using questionnaires distributed to respondents. Test the quality of the data by using the validity test, reliability test. Analysis using statistical calculations with multiple regression formula, partial test simultaneous test and the coefficient of determination. The results of the study showed that Work Skills had a significant effect on the performance appraisal of the Agriculture Office of the City of Pagar Alam. Work Commitment has no significant effect on the performance appraisal of the Pagar Alam City Agriculture Service employee. Work culture has no significant effect on the performance appraisal of the Pagar Alam City Agriculture Service employee. Work Skills have a significant effect on the effectiveness of the work of the Agriculture Office of the City of Pagar Alam. Work Commitment has a significant effect on the effectiveness of the work of the Agriculture Office of the City of Pagar Alam. Work culture has no significant effect on the work effectiveness of the Pagar Alam City Agriculture Service employees. Job Performance Assessment has a significant effect on the effectiveness of the work of the Pagar Alam City Agriculture Service employee.